2020
DOI: 10.1108/jpbafm-08-2019-0125
|View full text |Cite
|
Sign up to set email alerts
|

The institutionalization of public sector accounting reforms: the role of pilot entities

Abstract: PurposeThis paper aims at understanding the action of pilot entities, in order to ultimately infer about their role to the overall reform process of public sector accounting (PSA).Design/methodology/approachTaking the Portuguese case as a reference, the new institutional theory (isomorphism perspective) and institutional logics are used to explain the action and stance of pilot entities in the implementation process of reforms.FindingsPilot experiments are expected to provide feedback on the main difficulties … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 42 publications
0
12
0
4
Order By: Relevance
“…Regarding isomorphic pressures, in line with the extant literature, we found in our empirical analysis both isomorphic pressures and functional narratives for the implementation of IPSAS across countries, in the first place. Coercive and mimetic pressures (Jorge et al, 2020;Tagesson, 2015) were identified, i.e. the IPSAS either have been pushed by international organizations (such as the IMF in Iceland, in reacting to the financial crisis) or serve as an "orientation device" for issues where the IFRS remain silent (in UK; CIPFA, 2012).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding isomorphic pressures, in line with the extant literature, we found in our empirical analysis both isomorphic pressures and functional narratives for the implementation of IPSAS across countries, in the first place. Coercive and mimetic pressures (Jorge et al, 2020;Tagesson, 2015) were identified, i.e. the IPSAS either have been pushed by international organizations (such as the IMF in Iceland, in reacting to the financial crisis) or serve as an "orientation device" for issues where the IFRS remain silent (in UK; CIPFA, 2012).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Extant literature points towards functionalist (e.g. achieving higher performance: Brunsson et al, 2012, or receiving better conditions when borrowing on the credit market: Chytis et al, 2020) and institutionalist perspectives (coercive, normative and mimetic isomorphic pressures to gain and maintain organizational legitimacy; Jorge et al, 2020;Oulasvirta, 2014;Tagesson, 2015). Coercive pressures are particularly relevant for emerging economies (stemming from donor organizations), as, e.g.…”
Section: Standardization Deviations and Practice Variationmentioning
confidence: 99%
“…Following Jorge et al. (2020), pilot entities could be selected to develop training programs and understand the needs of accountants in the context of the forced adaption of digital technologies. The oversight authorities or international donors interested in pushing for digitalization may rely on compulsory transformation—initially focused on compliance—to foster the emergence of empowered departments and teams, and to promote visionary leaders who look forward to developing a comprehensive digital agenda.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the promoters of national projects could reflect on how to improve and amplify the project of digital transformation by extracting benefits from the compulsory approach; for instance, by considering an adequate level of organizing to deal with the digital developments implemented by the consignees. Following Jorge et al (2020), pilot entities could be selected to develop training programs and understand the needs of accountants in the context of the forced adaption of digital technologies.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Due to the gradual embedding of GRB into the budget system, with making use of pilot projects (Jorge et al, 2021), and the pre-existence of an Inter-Ministerial Working Group' and a Watch Group, the process of change can be characterized as 'incremental' (Streeck & Thelen, 2005) and not abrupt, which is also backed by the fact that the compositions of the circles for the RIAs (Figure 3) did not change significantly over time. However, regarding the results of change, it is not yet clear if the reform will eventually lead to a 'gradual transformation' of existing budget practices (Streeck & Thelen, 2005).…”
Section: Diffusion Stage 6-confirmation Of Grb?mentioning
confidence: 99%